Optimizing Qur’an Memorization in Pesantren through the Pomodoro Technique Based on Gagné’s Hierarchical Learning Framework - Bunga Shuhaila Rachmadini; Hilyah Ashoumi; Irwan Ahmad Akbar; M. Aliyul Wafa (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
This study aims to analyze the strategies of tahfidz teachers for overcoming challenges in memorizing the Qur’an at the Sunan Bonang Tahfidz Female Dormitory, Pesantren Mamba'ul Ma'arif, Denanyar, Jombang. Highlighting external challenges can deepen empathy for santri struggles (student in pesantren) and the importance of effective strategies. The research method used was a case study with a qualitative approach, involving observation, interviews, and documentation as data collection techniques. The results indicate that the tahfidz learning process at this pesantren is carried out in stages, starting from bi an-nadhor (reading by looking at the Mushaf), maqbul (memorizing the 30th juz and certain surah), and bi al-ghoib (memorizing without looking at the Mushaf). The results of this discussion indicate that applying the Pomodoro technique, combined with the Stepwise Learning theory and the Nine Events of Instruction by Robert Gagné, has proven effective in improving the quality, focus, and sustainability of the Qur'an memorization process at the Pesantren Sunan Bonang. This method provides a systematic, gradual, and mastery-oriented learning structure, while strengthening the processes of ziyadah, mura’jaah, and tasmi' through appropriate time management, repetition, and feedback.